Mediating role of spirituality in the relationship of anxiety, stress and depression with resilience in individuals exposed to earthquakes in Türkiye - Kerkez, Muejde; Sanli, Mehmet Emin (Elsevier, 2024)
This study aimed to determine whether spirituality mediates the relationship of anxiety, stress and depression with resilience in earthquake survivors. The study population composed of 616 individuals above the aged of 18 years and over who experienced the February 6 earthquake. Sociodemographic information was collected using the Depression Anxiety Stress Scale (DASS21), the Brief Psychological Resilience Scale (BRS), and the Spirituality Scale (SS). Through a path analysis model, it was found that spirituality importantly acted as a mediator in the connection between DASS-21 and BRS scores; the direct effect of DASS-21 scores on BRS scores was -0.575, their indirect effect through spirituality was -0.206, and the total effect size was -0.364. This research revealed that spirituality has a strong positive impact on resilience by reducing depression, anxiety and stress in catastrophic situations. In addition, this study revealed that spirituality could promote healthy coping strategies, especially in uncertain situations such as after earthquakes.
Keywords: Anxiety; Earthquake; Depression; Resilience; Stress; Spirituality